Mitigation of Corrosion Initiated by Cl− and SO42−ions in Blast Furnace Cement Concrete Mixed with Sea Water - Krivenko, Pavel; Rudenko, Igor; Konstantynovskyi, Oleksandr; Vaičiukynienė, Danutė (MDPI, 2022)
The use of blast furnace cement is an effective way to meet the requirements of sustainable development. However, CEM III/C is characterized by slow strength gain. The problem can be worse for plasticized reinforced blast furnace cement concretes mixed with sea water in view of shorter durability. The mitigation of corrosion in plasticized blast furnace cement concretes mixed with sea water can be provided through a composition of minor additional constituents, with percentage by mass of the main constituents: alkali metal compounds, 2…3; calcium aluminate cement, 1; clinoptilolite, 1. The alkali metal compounds are known to activate hydraulic properties of ground granulated blast furnace slag. A calcium aluminate cement promotes the accelerated chemical binding of Cl and SO-ions with the formation of Kuzel's salt. A clinoptilolite occludes these aggressive ions. The positive effects of the mentioned minor additional constituents in the blast furnace cement were supported by the increased early strength gain and the higher structural density, as well as by a good state of steel reinforcement, in the plasticized concretes mixed with sea water.
Keywords: blast furnace cement; corrosion; minor additional constituent; sea water; 691.3; 691.5